Discovery of artemisinin: The Chinese wonder drug - Padmaja Udaykumar (Wolters Kluwer Medknow Publications, 2014)
Artemisinin, a great boon to the patients of multidrug-resistant malaria, has an equally amazing history. Although used by the Chinese herbal healers centuries ago, its introduction to the modern system of medicine was preceded by extensive research. The success of 'project 523' is further evidence to the medical fraternity that collaborative research can yield rich dividends. Although many claim credit, Dr. Youyou Tu was awarded the Lasker prize for the feat.